Secondary successional patterns in an inter-andean dry tropical forest of Colombia: Implications for ecological restoration (2019)
The study of successional patterns and the trajectories followed by these in dry tropical forests is a fundamental aspect for guiding restoration processes on this important and threatened ecosystem. In an inter-Andean dry tropical forest of the upper Magdalena valley (Huila, Colombia), secondary successional patterns were identified through cluster analysis and nonmetric multidimensional scaling, for 171 plots of grasslands, shrubs, and forests grouped by age of abandonment. Seven floristic groups showing differences in structural and compositionspecies richness and basal area increased with the age of abandonment. Exclusive floristic groups were identified for each age class as well as some floristic groups that are shared throughout the succession. Four successional trajectories are proposed: two in areas with lower rainfall ranging from grasslands to shrubland, and forest with low values of floristic richness and less structural complexity; the other two in sectors with higher precipitation, ranging from grasslands to shrubs and forests with greater structural complexity and richness. We discussed how the defined trajectories and floristic groups could be considered as a basis for the establishment of flexible reference models for the monitoring and assessment of ecological restoration processes in the study area. © 2019, Universidad Nacional de Colombia. All rights reserved.